2022
DOI: 10.1186/s13020-022-00669-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel polysaccharide from red ginseng and its ameliorative effect on oxidative stress injury in myocardial ischemia

Abstract: Background Red ginseng (RG) was widely used as traditional Chinese medicine (TCM) or dietary supplement. However, few researches had been reported on the red ginseng polysaccharide (RGP). Methods In this study, a novel heteropolysaccharide named RGP1-1 was fractionated sequentially by DEAE-52 column and Sephadex G-100 gel column. The primary structure of RGP1-1, including glycosyl linkages, molecular weight, monosaccharide composition, morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…So, we speculated that there were a few arabinogalactan residues in SMP-AP. We concluded that SMP-AP is an acidic polysaccharide composed of glucan and RG-I pectin that has a small amount of arabingalactan linked to it as branched chains ( 39 ).…”
Section: Resultsmentioning
confidence: 98%
“…So, we speculated that there were a few arabinogalactan residues in SMP-AP. We concluded that SMP-AP is an acidic polysaccharide composed of glucan and RG-I pectin that has a small amount of arabingalactan linked to it as branched chains ( 39 ).…”
Section: Resultsmentioning
confidence: 98%